Community Organizing of Victims of Human Trafficking in Kulon Progo: Road to An Integrated Approach Against Oppression - Sri Widayanti (Sosio Konsepsia: Jurnal Penelitian dan Pengembangan Kesejahteraan Sosial, 2023)
The discourse on human trafficking and the efforts to overcome it are crucial issues that has received public attention in Indonesia and all around the globe. However, different perspectives among experts, activists and organizations gave rise to different approaches in analyzing the source of the problem, what is seen as the problem, and the intervention to solve the problem. This research focuses on community organizing of women victims of human trafficking as the approach which has been implemented to challenge oppression by Mitra Wacana Women Resource Center in Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta. This qualitative study is aimed to explore their perspectives on defining human trafficking and its complexities, their analysis of its causes and the intervention method. The theory of anti-oppressive is applied to analyze the data and findings within this research, which results in three main points; first, Mitra Wacana’s critical awareness raises a comprehensive perspective on the complexity of the human trafficking issue by identifying the community as victims of a discriminatory and exploitative system. Second, organizing ex-migrant workers in Pusat Pembelajaran Perempuan dan Anak/P3A (Learning Center for Women and Children) is applied as the approach to strengthen rights-based capacity for the Kulon Progo community. Third, an integrated approach against oppression within human trafficking tried to synergize three levels of personal, cultural and structural approach. In the case of human trafficking in Kulon Progo, the integrated approach consists of public education, information development, and policy advocacy on humanity issues by involving the organization of ex-migrant workers.